Manufacturing (co)agglomeration in a transition country: Evidence from Russia - Ekaterina Aleksandrova; Kristian Behrens; Maria Kuznetsova (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We document geographic concentration patterns of Russian manufacturing using microgeographic data. About 42-52% of 4-digit and 63-75% of 3-digit industries are localized, with a higher share in the European part than in the Asian part. About 70% of 3-digit industry pairs are coagglomerated, especially those with stronger buyer-supplier links, more knowledge sharing, and lower transport costs. Pairs with a more similar workforce are, however, less coagglomerated, which points to impediments in labor mobility between regions and firms. Overall, the agglomeration forces are fairly similar to those operating in developed countries, with transportation likely to be a key driver.
Keywords: 330